Motivation Of Pregnant Women In The First Trimester In Undertaking Antenatal Care (Anc) Examinations At Hospital X - Vivi Nurhaliza; Roza Indra Yeni; Rima Berlian Putri; Ricky Riyanto Iksan (Jurnal Life Birth, 2026)
Background: The Maternal Mortality Rate (MMR) in Indonesia is still relatively high and is one of the main problems in the field of maternal and child health. Strategic efforts that can be made to reduce MMR are through optimal implementation of Antenatal Care (ANC), especially in the first trimester of pregnancy. Early ANC examinations play an important role in detecting risk factors and pregnancy complications. However, the coverage of ANC visits in the first trimester is still not optimal, one of which is influenced by the level of motivation of pregnant women. Motivation is an internal factor that plays a role in encouraging awareness, willingness, and compliance of pregnant women to undergo routine pregnancy checks. This study aims to determine the description of the motivation of pregnant women in the first trimester in conducting Antenatal Care (ANC) visits at Hospital X. This study used a quantitative method with a sample of 62 respondents. The research instrument was a motivation questionnaire, while data analysis was carried out univariately. The results showed that the majority of pregnant women had good and fairly good motivation, each amounting to 60 pregnant women (48.4%), but there were still 2 pregnant women (3.2%) respondents with poor motivation. In conclusion, the motivation of pregnant women in the first trimester is quite good, so it is necessary to make continuous efforts through providing education and support by health workers..